2013
DOI: 10.1080/09654313.2013.835793
|View full text |Cite
|
Sign up to set email alerts
|

Combining Knowledge from Different Sources, Channels and Geographical Scales

Abstract: The aim of this article is to examine conceptually and empirically how innovative firms combine knowledge (1) provided by different sources, (2) accessed at different spatial scales, and (3) acquired through different channels. We add to the conceptual debate by contrasting and synthesizing the perspectives offered on these issues by four key concepts, namely the local buzz and global pipelines argument, the knowledge base approach, the notions of STI and DUI modes of innovation as well as the regional innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 34 publications
3
52
0
4
Order By: Relevance
“…However, these studies also demonstrated more complex patterns of innovation bringing forward evidence for the combinaton of knowledge bases in many of those sectors (Halkier et al 2010). Similar arguments and findings were presented by Crevoisier and Jeannerat (2009), , Grillitsch and Trippl (2013), Manniche (2012), Strambach and Klement (2012). In particular the report on the EURODITE project (Halkier et al 2010, p. 52 ff) is of interest here.…”
Section: Combining Knowledge Basessupporting
confidence: 63%
See 1 more Smart Citation
“…However, these studies also demonstrated more complex patterns of innovation bringing forward evidence for the combinaton of knowledge bases in many of those sectors (Halkier et al 2010). Similar arguments and findings were presented by Crevoisier and Jeannerat (2009), , Grillitsch and Trippl (2013), Manniche (2012), Strambach and Klement (2012). In particular the report on the EURODITE project (Halkier et al 2010, p. 52 ff) is of interest here.…”
Section: Combining Knowledge Basessupporting
confidence: 63%
“…This to some extent is a further development of Camagni's argument, since it also demonstrates the benefit of combining local and global knowledge relations. It also suffers from too strong simplifications as was pointed out by Trippl et al (2009) and by Grillitsch and Trippl (2013).…”
Section: Multilevel Perspectivementioning
confidence: 99%
“…Over the past 20 years, four key approaches to knowledge systems have been discussed: (1) the knowledge-based approach; (2) the Science-Technology-Innovation (STI) and Doing-Using-Interacting (DUI) modes of innovation; (3) the regional innovation systems (RIS) concept; and (4) the local buzz and global pipelines argument [1]. However, the core weaknesses of these approaches are that they are mainly derived from innovation and creative clusters in Europe and North America, which cannot be transplanted to developing economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The emphasis on studying the knowledge management of industrial clusters has gradually shifted to cluster knowledge transference and knowledge channels in knowledge networks [1]. As a channel for acquiring and improving crafts and skills, apprenticeship systems have had much significance to local, traditional, craft-based clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation